2022
DOI: 10.1177/00380407211070319
|View full text |Cite
|
Sign up to set email alerts
|

Schools as a Relatively Standardizing Institution: The Case of Gender Gaps in Cognitive Skills

Abstract: Growing evidence suggests that contrary to popular belief, schools mostly do not generate achievement gaps in cognitive skills but, rather, reflect the inequalities that already exist. In the case of socioeconomic status, exposure to school often reduces gaps. Surprisingly little is known, however, about whether this pattern extends to gender gaps in cognitive skills. We compare how gender gaps in math and reading change when children are in school versus out (in the summer) among over 900,000 U.S. children. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 62 publications
4
11
1
Order By: Relevance
“…The results indicated that both the school and non-school environments contribute to an increase in the gender gap in academic achievement. This finding is in stark contrast to a study by Downey, Kuhfeld, and van Hek (2022), who found that schools help equalize the gender gap in the US. I can only speculate as to the reason for this difference in results, but it could be due to some overall differences between school culture in Denmark and the US.…”
Section: Discussioncontrasting
confidence: 99%
“…The results indicated that both the school and non-school environments contribute to an increase in the gender gap in academic achievement. This finding is in stark contrast to a study by Downey, Kuhfeld, and van Hek (2022), who found that schools help equalize the gender gap in the US. I can only speculate as to the reason for this difference in results, but it could be due to some overall differences between school culture in Denmark and the US.…”
Section: Discussioncontrasting
confidence: 99%
“…Teachers can treat boys and girls differently and have been found to develop more adversarial relationships with children from working-class backgrounds (Smyth, 2018). Other research suggests, however, that schools may have an equalizing effect, narrowing the gap in test scores between boys and girls (Downey et al, 2022). This all suggests that the effect of exposure to school may have a different impact on girls and boys, and on children from different social class backgrounds.…”
Section: Early Childcare and Educationmentioning
confidence: 99%
“…If schools reduce gender inequality, differences in reading behavior between girls and boys are likely smaller during school hours than when children structure their own time. However, because studies such as Downey et al (2022) do not provide empirical evidence on students' concrete learning behavior, we lack knowledge about how children's achievement‐related behavior differs by gender when school is in or out. Studies drawing on self‐reported time use of teenagers (age 15–17) indicate that girls study more for school and spend more time reading for leisure than boys do (OECD, 2015; Wight et al, 2009)—both on school days and when school is out (Wight et al, 2009).…”
mentioning
confidence: 99%
“…In this context, it has been suggested that schools' reading curriculum is often more aligned with the interests of girls (Coles & Hall, 2002), and the primarily female teaching staff implicitly communicate that reading is a predominantly female domain (Millard, 1997). However, recent analyses of changes in gender gaps during summer holidays for primary and secondary school students have shown that gender inequality in academic achievement cannot be attributed to periods when school is in session (Downey et al, 2022). If schools reduce gender inequality, differences in reading behavior between girls and boys are likely smaller during school hours than when children structure their own time.…”
mentioning
confidence: 99%
See 1 more Smart Citation